Farm Crime and Farmer-Police Relationships in Rural Australia - Mulrooney, Kyle; Harkness, Alistair; Nolan, Huw (International Journal of Rural Criminology, 2022)
This article presents select findings from ‘farm crime’ victimisation surveys undertaken in the two most populous Australian states of New South Wales and Victoria. We examine the findings in relation to farmer crime victimisation, their willingness to report crime, and their worry about crime, as well as farmer perspectives on policing generally and the policing of farm crime specifically. In both states, there are high levels of victimisation, high levels of worry, low- to mid-levels of confidence in the police, and there remains a gap between experiences of farm crime and reporting. Both states have police tasked specifically with addressing farm crime. The Victoria Police have Farm Crime Liaison Officers that specialise in assisting with farm related crimes, however this is a voluntary role which forms part of an officer’s larger workload. By contrast, the New South Wales Police Force Rural Crime Prevention Team is a dedicated team consisting of specialised rural crime investigators and intelligence practitioners focused on proactive and preventative interventions in farm crime. Farmers in both states were surveyed regarding their awareness and engagement with these rural policing teams, and we examined how this may shape victimisation, reporting, worry and the relationships between police and farmers. In New South Wales, awareness and direct contact with rural crime police led to both increased satisfaction with police and crime reporting. Respondents with awareness of this team also express significantly less worry of crime, whilst those with direct contact did not. We conclude the article by discussing and contextualising these findings within rural criminology and considering ways forward for the policing of farm crime.